Semantic Cloud: Building Dynamic Mashup in Cloud Environment - Malki, Abdelhamid; Benslimane, Sidi Mohammed (International journal of information technology and web engineering, 2013)
Mashups allowed a significant advance in the automation of interactions between applications and Web resources. In particular, the combination of web Application Programming Interfaces (APIs) is seen as a strength, which can meet the complex needs by combining the functionality and data from multiple services within a single Mashup application. Automating the process of building Mashup based mainly on the Semantics Web APIs which facilitate to the developer their selection and matching. In this paper, we introduce reference architecture with six layers representing the main functional blocks for annotating, combining and deploying Web APIs in Cloud environment. We introduce Semantic Annotation for Web Application Description Language (SAWADL), an extension of the Web Application Description Language (WADL) that allows the semantization of the REST Web Service. The proposed architecture uses the Cloud Computing technology as a promising solution to increase the number of public API and therefore making the engineering process of Mashup applications more agile and more flexible.